2010
DOI: 10.1103/physrevb.81.174504
|View full text |Cite
|
Sign up to set email alerts
|

Optical model-solution to the competition between a pseudogap phase and a charge-transfer-gap phase in high-temperature cuprate superconductors

Abstract: We present a theoretical framework for a quantitative understanding of the full doping dependence of the optical spectra of the cuprates. In accord with experimental observations, the computed spectra show how the high-energy Mott features continue to persist in the overdoped regime even after the mid-infrared (MIR) peak originating from the pseudogap has collapsed in a quantum critical point. In this way, we reconcile the opposing tendencies of the MIR and Mott peaks to shift in opposite directions in the opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…A similar intermediate coupling theory has been successful in describing many saliant features in cuprates. 41,42 Recently, we became aware of the works by Wang et al 40 and Maier et al 43 which also predicted the d-wave gap in FeSe based systems.…”
Section: Discussionmentioning
confidence: 99%
“…A similar intermediate coupling theory has been successful in describing many saliant features in cuprates. 41,42 Recently, we became aware of the works by Wang et al 40 and Maier et al 43 which also predicted the d-wave gap in FeSe based systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, λ has a strong momentum dependence, for instance, the nodal value is considerably smaller: in LSCO, λ nodal = 0.14-0.22 at optimal doping, and 0.14-0.20 in the overdoped regime [39]. Since nodal electrons dominate transport [16], this accounts for the smaller λʼs estimated from transport measurements. Further, several calculations suggest that correlation effects can enhance the anisotropy of electron-phonon coupling, generally leading to a larger value for AN nesting [28,[43][44][45].…”
Section: Model and Formalismmentioning
confidence: 99%
“…We adopt an intermediate coupling approach in our analysis in this study [13]. This is justified by recent studies [14][15][16][17][18][19], which have indicated that correlations in the cuprates are not as strong as initially believed, and that cuprates fall, instead, in an intermediate coupling regime, with ⩽ ⩽ U t 6 9 , where U is the effective Hubbard interaction and t is the nearest-neighbor hopping parameter. We have shown [13] that intermediate coupling corresponds approximately to ⩽ ⩽ = U t U t 4 13.6 BR , where U BR is the mean-field Brinkman-Rice energy signaling the transition to the Mott insulating state [15,20].…”
Section: Introductionmentioning
confidence: 98%
“…4 An advantage of the intermediate coupling method is that the diagrammatic perturbation theory of fluctuations can still be applied as long as the Hubbard (Coulomb) U~D, where D is the non-interacting bandwidth. 5,6 Here one starts from the itinerant band picture of electrons where dynamic correlation effects are added perturbatively, giving rise to strong electronic structure renormalization. The fluctuation theory becomes exact in the weak coupling regime, but is rather complicated to treat in the intermediate regime.…”
Section: Introductionmentioning
confidence: 99%